2021
DOI: 10.1037/cdp0000461
|View full text |Cite
|
Sign up to set email alerts
|

Latinx adolescents facing multiple stressors and the protective role of familismo.

Abstract: Objective: In this study, we cumulatively examined how a number of cultural and general stressors as well as familismo differentially related to Latinx adolescents' psychological well-being as measured by depressive symptoms, anxiety, and future orientation. In addition, we examined whether familismo buffered Latinx adolescents from the negative psychological outcomes associated with both cultural and general stressors. Method: Two hundred and twenty-four low-income, Latinx 9th graders (M age = 14.5) attending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 67 publications
(114 reference statements)
3
6
0
Order By: Relevance
“…The presence of economic hardship in a Latinx adolescent’s life can increase exposure to other stressors and, in-turn, poorer psychological outcomes (Montoro & Ceballo, 2021). In the present study, this concept was demonstrated by the interaction of food insecurity and role overload and its relationship to the experience of depressive symptoms among Latinx adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of economic hardship in a Latinx adolescent’s life can increase exposure to other stressors and, in-turn, poorer psychological outcomes (Montoro & Ceballo, 2021). In the present study, this concept was demonstrated by the interaction of food insecurity and role overload and its relationship to the experience of depressive symptoms among Latinx adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Winkelman et al (2017) suggest a possible explanation for these differences—that socioeconomic disadvantage, rather than mental health problems, may be the dominant driver of justice involvement for BIPOC youth. Alternatively, cultural values such as familismo (an important value in some Latinx cultures) may increase resilience and buffer the mental health effects of external stressors for some BIPOC youth (Montoro & Ceballo, 2021). Another possibility is that BIPOC youth may feel less comfortable disclosing sensitive experiences in research settings due to concerns about confidentiality or discrimination (Johnson & Richter, 2004; Kerig et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, familism values are generally directly associated with positive adaptation among Latine youth (Cahill et al, 2021; Stein et al, 2014). Latine youth with strong familism values report more positive parent–adolescent relationships (Delgado et al, 2011; Lorenzo-Blanco et al, 2012; Taylor et al, 2012), lower levels of family conflict (Smokowski et al, 2010), and lower levels of depressive symptoms (Dixon De Silva et al, 2020; Montoro & Ceballo, 2021; Piña-Watson et al, 2019).…”
Section: Immigration-related Stressors and Latine Youth Depressive Sy...mentioning
confidence: 99%
“…Beyond the direct effects of familism values on family relationships and adolescent well-being, familism values may also moderate the effects of family conflict. Indeed, some research indicates that familism values protect against youth depressive symptoms in the context of family stress (e.g., Montoro & Ceballo, 2021; Piña-Watson et al, 2019). However, other studies have found no evidence of a moderating effect (Ayón et al, 2010; Delgado et al, 2011; Hurwich-Reiss & Gudiño, 2016; Stein et al, 2015; Umaña-Taylor et al, 2011), and a few studies indicate that strong familism values might have deleterious effects in some instances (Hernández et al, 2010; Kuhlberg et al, 2010).…”
Section: Immigration-related Stressors and Latine Youth Depressive Sy...mentioning
confidence: 99%